Young people’s sense of agency and responsibility towards promoting mental health in Brazil: a reflexive thematic analysis - Ilina Singh; Gabriela Pavarini; Felipe Rodrigues Siston; Sheila Giardini Murta; Josimar Antônio de Alcântara Mendes; Julyana Alves Ferreira; Victor Hugo de Lima Santos; Brenda Thallys Rocha Seabra; Rafa Ribeiro Alves de Souza; Rafaela de Oliveira da Cunha (BMJ Open)
Objectives This study investigated how Brazilian young people perceive their role in promoting and supporting their peer community’s mental health and well-being, and the conditions and contexts influencing their engagement.Design Co-produced qualitative study using in-depth interviews and focus groups with adolescents. The sessions were audio-recorded, transcribed and anonymised. Data were analysed using reflexive thematic analysis.Setting Data collection took place remotely across Brazil via audio or video calls conducted by a youth collaborator and a senior researcher.Participants 46 Brazilian adolescents aged between 15 and 18 years old, recruited primarily via social media.Results Our analysis generated four overarching themes: (1) young people’s sense of responsibility and motivation—many participants felt committed to promoting the mental health and well-being of their friends and community, while also critically emphasising responsibilities of and partnerships with adult stakeholders to make a meaningful difference; (2) strategies for promoting peer mental health—suggested strategies included peer-to-peer support, such as non-judgemental listening, and collective actions such as forming school groups; (3) intrapersonal barriers—key barriers to participation included a lack of necessary skills and self-efficacy; and (4) contextual barriers—young people reported feeling unheard, invalidated, and fearing judgement due to mental health stigma.Conclusion These findings support an ecological view of youth participation in the promotion of mental health as dependent on intrapersonal, interpersonal and contextual factors. Realising young people’s potential in advancing mental health in their communities requires fostering youth–adult partnerships, providing peer support training, and combating adultism and mental health stigma.